Imagination, Multimodality, and Sound - Braga, Joaquim (2019)
Joaquim Braga deals with the role of sound in multimodal environments and multimodal surfaces. He argues that imagination not only bridges sensory dimensions that are absent from perception but also is central to “the relationship of presence,” that is, the connection between presently perceived sensory input. This involves assessing both the individuating dimension and the relational disposition of sound, which allows sound—through the activation of imagination—to develop sensory relations. Central to his discussion of the function and contribution of sound in different media is the process of “sonic individuation”—a process of individuation of different modalities—that is presented as a precondition for the creation of relations between these modalities.